1993
DOI: 10.1002/jor.1100110203
|View full text |Cite
|
Sign up to set email alerts
|

In vivo effects of naproxen on composition, proteoglycan metabolism, and matrix metalloproteinase activities in canine articular cartilage

Abstract: Naproxen is a nonsteroidal anti-inflammatory drug commonly used in the clinical treatment of joint disease. In this study, its effect in vivo on the biochemical composition, metabolic activities, and metalloproteinase activities of normal canine articular cartilage was analyzed. The articular cartilage from the knee joints of dogs who had been given naproxen for 4 weeks to maintain a serum level of 40-50 micrograms/ml was examined. Control animals were given a placebo. Treatment with naproxen was not found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 52 publications
(71 reference statements)
0
12
0
Order By: Relevance
“…At least 4 other drugs that inhibit prostaglandin synthesis have been examined in the OA dog model. Tiaprofenic acid (36) and diclofenac (this study) showed modest activity, naproxen may affect some biochemical parameters (37), and aspirin accel-erated the development of severe OA (38). Thus, we think it unlikely that the effects of tenidap reported herein are simply due its inhibitory activity on prostaglandin synthesis.…”
Section: Discussionmentioning
confidence: 90%
“…At least 4 other drugs that inhibit prostaglandin synthesis have been examined in the OA dog model. Tiaprofenic acid (36) and diclofenac (this study) showed modest activity, naproxen may affect some biochemical parameters (37), and aspirin accel-erated the development of severe OA (38). Thus, we think it unlikely that the effects of tenidap reported herein are simply due its inhibitory activity on prostaglandin synthesis.…”
Section: Discussionmentioning
confidence: 90%
“…Recently, Pelletier et al reported that the NSAID, carprofen, reduced the structural changes and abnormal bone metabolism in an experimental dog OA model (51). In addition, some reports have shown positive effects of NSAIDs on cartilage integrity through suppression of proteoglycan degradation in vitro (52, 53) and in vivo (54, 55). In contrast, several reports indicate that these compounds do not have any positive effect on IL‐1β‐stimulated proteoglycan degradation (38, 53).…”
Section: Discussionmentioning
confidence: 99%
“…According to reports in the literature (Arumugham and Bose, 1981;Goodman et al, 2002;Muscará et al, 2000;Ratcliffe et al, 1993;Sadowski and Steinmeyer, 2001;Smith et al, 1995;Solheim et al, 1986;Srinivas et al, 1994), naproxen may affect, or not, the collagen synthesis in mammals depending on the dose applied. Böckelmann and Bechara (2004) and that failing, to alter the regeneration of the carp tail fin (10.4 mg.L -1 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is used in the treatment of osteoarthritis, rheumatoid arthritis, gout and rheumatism of soft tissue and is also indicated for periarticular and musculoskeletal diseases (Hanson et al, 2005;Mendias et al, 2004;Ratcliffe et al, 1993).…”
Section: Ultrastructural Processmentioning
confidence: 99%
See 1 more Smart Citation